Application and Significance of the Sadharanikaran Model of Communication (SMC) in Foreign Language Pedagogy - Su, Zhengju (Bodhi: An Interdisciplinary Journal, 2024)
This paper examines the Sadharanikaran Model ofCommunication (SMC) and its application in foreignlanguage pedagogy. Rooted in Indian philosophy, SMCoffers a holistic view of communication, emphasizing theinterplay between the communicator, message, andrecipient. It posits that communication is influenced bycultural and social contexts, which can enhance languageteaching by promoting a learner-centered approach. Byintegrating SMC principles into language curricula, teachingmaterials, and classroom activities, educators can foster adeeper understanding of communication processes and adapttheir methodologies accordingly.The study highlights the benefits of using authenticmaterials and creating inclusive learning environments toimprove language acquisition and cross-culturalunderstanding among students. It explores how SMCprinciples can facilitate language learning as a dynamic and interactive process, encouraging educators to adoptstrategies that value the unique experiences and perspectivesof each student. By promoting cultural empathy andintercultural sensitivity, SMC provides a framework forcultivating communicative competence and enhancing theoverall effectiveness of foreign language education.